Method for in-situ growth of ZIF-7 film layer on surface of magnesium alloy micro-arc oxidation film layer
By growing the ZIF-7 film layer in situ on the surface of the magnesium alloy microarc oxide film layer, the problem of the magnesium alloy microarc oxide film layer is easily shedded or failed during long-term use, significantly improving the corrosion resistance of the magnesium alloy and the denseness of the film layer, reducing operational complexity and cost.
Patent Information
- Application Number
- CN202411820417.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-14
AI Technical Summary
The magnesium alloy microarc oxide film layer is prone to fall off or fail during long-term use, lacks hardness and toughness, and has poor corrosion resistance.
The ZIF-7 film layer was grown in situ on the surface of the microarc oxide film layer of magnesium alloy, and a sheet-like ZIF-7 film layer was formed by the reaction of zinc nitrate hexahydrate and benzimidazole in N,N-dimethylformamide and methanol.
It significantly improves the corrosion resistance of magnesium alloy, enhances the density and uniformity of the film layer, reduces the complexity and cost of operation, and meets environmental protection requirements.
Smart Images

Figure CN119615330A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of micro-arc oxidation composite film layers, and in particular to a method for in-situ growing a ZIF-7 film layer on the surface of a magnesium alloy micro-arc oxidation film layer. Background Art
[0002] Magnesium alloy is a high-performance lightweight structural material based on magnesium, which has the advantages of low density, high strength and good rigidity. However, the high chemical and electrochemical activity of magnesium alloy and the resulting poor corrosion resistance have always been the main bottleneck restricting its widespread application. Micro-arc oxidation surface treatment technology, which induces arc discharge on the surface of metals and their alloys by applying high voltage in the electrolyte, thereby in situ generating a ceramic film layer mainly composed of matrix metal oxides, which can form a dense oxide film and significantly improve the surface hardness and corrosion resistance of the material. However, during the micro-arc oxidation process, holes and cracks are easily formed on the surface of the coating. These defects will become channels for the penetration of corrosive media and affect the performance of the coating. Traditional sealing technologies may include organic sealing, sol-gel method, electrochemical sealing, etc. The main purpose of these methods is to fill the pores in the micro-arc oxidation film layer and improve the density and corrosion resistance of the film layer. However, these methods can only partially fill the pores, and the stability and durability of the sealing materials are limited. They are prone to fall off or fail in long-term use, and ultimately lead to problems such as incomplete sealing, uneven sealing quality, or poor bonding between the sealing layer and the substrate. This series of problems leads to insufficient hardness and toughness of the micro-arc oxidation film layer after sealing, and poor corrosion resistance. Summary of the invention
[0003] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a method to solve the problems in the prior art of poor wind control effect of micro-arc oxidation film on magnesium alloy, easy to fall off or fail during long-term use, insufficient hardness and toughness, and poor corrosion resistance.
[0004] In order to solve the above technical problems, this application adopts the following technical solutions:
[0005] A method for in-situ growing a ZIF-7 film layer on the surface of a magnesium alloy micro-arc oxidation film layer comprises the following steps:
[0006] Step 1: Process the surface of the magnesium alloy workpiece to be processed to make the surface smooth;
[0007] Step 2: placing the workpiece treated in step 1 as an anode in an electrolyte, using graphite as a cathode, and performing micro-arc oxidation treatment on the workpiece using a DC power supply in a constant current mode to form a micro-arc oxidation film layer on the surface of the workpiece, followed by cleaning and drying;
[0008] Step 3: Place the workpiece prepared in step 2 into the ZIF-7 seed solution, keep it at 110-130°C for 180-300 minutes for in-situ growth, take it out after the growth is completed, and wash and dry it;
[0009] The ZIF-7 seed solution includes zinc nitrate hexahydrate and benzimidazole, and the solvent is N,N-dimethylformamide and methanol; in the ZIF-7 seed solution, the concentration of zinc nitrate hexahydrate is 0.5-2.5 g / L, and the concentration of benzimidazole is 0.5-2.5 g / L.
[0010] Preferably, in step 2, the electrolyte comprises sodium silicate, sodium hydroxide and sodium fluoride; wherein, in the electrolyte, the concentration of sodium silicate is 5-10 g / L, the concentration of sodium hydroxide is 1-4 g / L, and the concentration of sodium fluoride is 1-4 g / L.
[0011] Preferably, the ZIF-7 seed solution is obtained by the following steps:
[0012] Dissolve zinc nitrate hexahydrate in N,N-dimethylformamide solution as solution A;
[0013] Subsequently, benzimidazole was dissolved in methanol of the same mass as that of solution A to obtain solution B; wherein the concentration of methanol was analytical grade.
[0014] Then, liquid A is slowly added into liquid B while stirring continuously, and the ZIF-7 seed solution is obtained by mixing.
[0015] Preferably, in step 3, the temperature is preferably 110°C.
[0016] Preferably, in step 3, the insulation time is preferably 240 min.
[0017] Preferably, in step 1, the surface of the magnesium alloy workpiece is polished to make the surface smooth using water-abrasive sandpaper with mesh sizes of 180#, 400#, 600#, 1200# and 2000#, respectively.
[0018] Preferably, in step 2, the electrolyte is continuously stirred at a rotation speed of 800 rpm.
[0019] Preferably, in step 2, the conditions of micro-arc oxidation treatment are as follows:
[0020] Current density is 6~10A / dm 2 , frequency is 500-800 Hz, duty cycle is 10%-50%, and micro-arc oxidation time is 5-15 min.
[0021] Compared with the prior art, this application has the following beneficial effects:
[0022] 1. The method described in the present application effectively solves the problem of incomplete sealing in traditional sealing technology by in-situ growing a ZIF-7 film on the surface of a magnesium alloy micro-arc oxidation film. The growth process of the ZIF-7 film is carried out under specific reaction conditions by zinc nitrate hexahydrate and benzimidazole in a mixed solvent of N,N-dimethylformamide and methanol. Since the obtained ZIF-7 film has a highly ordered porous structure and good chemical stability, it can evenly cover and fill the micropores on the surface of the MAO film. It is particularly worth mentioning that the formed ZIF-7 film has a flaky structure, which enables ZIF-7 to better fit the surface of the MAO film to form a denser and more uniform protective layer. The ZIF-7 film with a flaky structure can not only physically block the penetration of corrosive media, but also adsorb and release corrosion inhibitors through its internal pore structure to achieve dynamic protection, significantly enhancing the corrosion resistance of magnesium alloys.
[0023] 2. The operation process of the method described in the present application is simple, and the seed solution system composition is simple, which can effectively reduce costs. Traditional sealing methods usually require complicated pre-treatment and post-treatment steps, such as high-temperature hot water treatment, organic sealing and inorganic salt sealing, etc. These methods are not only time-consuming and laborious, but also require a large amount of chemicals and energy. In contrast, the process of in-situ growth of ZIF-7 film in the method described in the present application is relatively simple, and only requires the treated magnesium alloy workpiece to be placed in a specific seed solution and kept warm for a period of time at a suitable temperature. This simplified method not only reduces the operating steps, reduces production costs, but also improves production efficiency. In addition, the seed solution system composition used in the present application is simple, easy to prepare and control, and further reduces material costs. The ZIF-7 film with a sheet structure is easier to control its uniformity and thickness during the growth process, further simplifying the process flow.
[0024] 3. The process of the method described in this application is environmentally friendly and meets the environmental protection requirements of modern industrial production. The chemicals used in traditional sealing methods may contain harmful substances, posing potential risks to the environment and human health. However, the synthesis of ZIF-7 in this application uses non-toxic and harmless raw materials, and the synthesis process is relatively mild and does not produce harmful waste.
[0025] 4. This application not only significantly improves the sealing effect and enhances the corrosion resistance of the magnesium alloy by in-situ growing a ZIF-7 film on the surface of the magnesium alloy micro-arc oxidation film, but also simplifies the operation process, reduces costs, and meets environmental protection requirements. In particular, the formed ZIF-7 film has a flaky structure, which further improves the density and uniformity of the film, making this method have important application value and development potential in the field of magnesium alloy surface treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The microscopic morphology of the film surface prepared in Example and Comparative Example 1; wherein a is Comparative Example 1, b is Example 1, c is Example 2, d is Example 3, and e is Example 4.
[0027] Figure 2 This is the XRD pattern of the ZIF-7 film layer prepared in Example 1.
[0028] Figure 3 The graph is a graph of electrochemical impedance test results of the film layers prepared in the examples and comparative examples. DETAILED DESCRIPTION
[0029] This application will combine the drawings in the embodiments of this application to clearly and completely describe the technical solutions in the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on this application belong to the scope of protection of this application.
[0030] Unless otherwise indicated in specific cases in this application, the numerical ranges listed herein include the upper and lower limits, as well as all integers and fractions within the range, and are not limited to the specific values listed when defining the range.
[0031] 1. A method for in-situ growth of a ZIF-7 film on the surface of a magnesium alloy micro-arc oxidation film
[0032] Step 1: Process the surface of the magnesium alloy workpiece to be processed to make the surface smooth;
[0033] Step 2: placing the workpiece treated in step 1 as an anode in an electrolyte, using graphite as a cathode, and performing micro-arc oxidation treatment on the workpiece using a DC power supply in a constant current mode to form a micro-arc oxidation film layer on the surface of the workpiece, followed by cleaning and drying;
[0034] Step 3: Place the workpiece prepared in step 2 into the ZIF-7 seed solution, keep it at 110-130°C for 180-300 minutes for in-situ growth, take it out after the growth is completed, and wash and dry it;
[0035] The ZIF-7 seed solution includes zinc nitrate hexahydrate and benzimidazole, and the solvent is N,N-dimethylformamide and methanol; in the ZIF-7 seed solution, the concentration of zinc nitrate hexahydrate is 0.5-2.5 g / L, and the concentration of benzimidazole is 0.5-2.5 g / L.
[0036] Sealing the surface of magnesium alloy micro-arc oxidation (MAO) film is an important means to improve the corrosion resistance and surface properties of magnesium alloy. However, the existing sealing technology has some obvious limitations, which limit the wide application of magnesium alloy in the field of high performance to a certain extent. Traditional sealing methods mainly include hot water sealing, organic sealing and inorganic salt sealing. Although these methods can improve the compactness and corrosion resistance of MAO film to a certain extent, they often have problems such as incomplete sealing, limited stability and durability of sealing materials, complex operation and environmental pollution. For example, the hot water sealing method may only partially fill the pores and easily lead to thermal degradation of the film under high temperature conditions; the organic sealing method may introduce harmful substances, posing potential risks to the environment and human health; the inorganic salt sealing method may affect the overall performance of the film due to the insufficient mechanical properties of the sealing material. To this end, the present application conceives a strategy to in situ grow a ZIF-7 film on the surface of magnesium alloy micro-arc oxidation film. ZIF-7 (zeolite imidazolate framework structure-7) is a highly ordered metal organic framework material with excellent chemical stability and thermal stability. By in-situ growing ZIF-7 film on the surface of MAO film, not only can the pores be covered and filled more evenly, the compactness and corrosion resistance of the film can be improved, but also dynamic protection can be achieved through the pore structure inside it, further enhancing the comprehensive performance of magnesium alloy. In order to achieve this purpose, the present application adjusts the growth method of ZIF-7 film, and by controlling the growth conditions, the ZIF-7 film is grown in-situ on the surface of MAO film. The present application further finds that the ZIF-7 film formed by the method is a sheet-like structure. Compared with the common nano-scale particles or micron-scale polyhedrons in the prior art, the ZIF-7 film with a sheet-like structure can better fit the surface of the MAO film to form a more compact and uniform protective layer. This structure can not only physically block the penetration of corrosive media, but also adsorb and release corrosion inhibitors through its internal pore structure, achieve dynamic protection, and significantly enhance the corrosion resistance of magnesium alloy. In addition, the ZIF-7 film with a sheet-like structure is easier to control its uniformity and thickness during the growth process, further simplifies the process flow, and improves production efficiency.
[0037] In some embodiments of the present application, in step 3, the workpiece prepared in step 2 is placed in a ZIF-7 seed solution, and is kept at 110°C to 130°C for 180min to 300min for in-situ growth. After the growth is completed, the workpiece is taken out and cleaned and dried. When the growth temperature is too low or the growth time is too short, ZIF-7 cannot be effectively grown on the micro-arc oxidation coating; when the growth temperature is too high or the growth time is too long, the micro-arc coating will be dissolved; in order to ensure that ZIF-7 can effectively grow on the surface of the micro-arc coating, and this process will not cause the coating to dissolve, the growth temperature can be 110°C, 120°C, 130°C, etc., and all ranges and sub-ranges between the above values; the holding time can be 180min, 240min, 300min, etc., and all ranges and sub-ranges between the above values; it should be understood that in the implementation scheme, any of the above ranges can be combined with any other ranges.
[0038] In some embodiments of the present application, the ZIF-7 seed solution includes zinc nitrate hexahydrate and benzimidazole, and the solvent is N,N-dimethylformamide and methanol; in the ZIF-7 seed solution, the concentration of zinc nitrate hexahydrate is 0.5-2.5 g / L, and the concentration of benzimidazole is 0.5-2.5 g / L. Among them, zinc nitrate hexahydrate is used as a zinc source, and benzimidazole is used as a ligand. The ligand can provide chemical and thermal stability, adjust the air-conducting properties, and enhance the functionalization of ZIF-7 materials in the synthesis of ZIF-7. The zinc nitrate hexahydrate and benzimidazole are controlled within this range to ensure that a sufficient amount of ZIF-7 can be generated on the surface of the micro-arc oxidation coating. If it is lower than the concentration described in this application, the amount of ZIF-7 generated will be insufficient, and the technical effect described in this application cannot be achieved; if it is higher than the concentration described in this application, the raw materials will react with the coating, which will also result in insufficient amount of ZIF-7 generated and damage the original coating. If other ligand compounds are used for the reaction, for example, 2-methylimidazole will not generate ZIF-7, but will generate ZIF-8. Therefore, the concentration of zinc nitrate hexahydrate can be 0.5 g / L, 1.0 g / L, 1.5 g / L, 2.0 g / L, 2.5 g / L, etc., and all ranges and sub-ranges between the above values; the concentration of benzimidazole can be 0.5 g / L, 1.0 g / L, 1.5 g / L, 2.0 g / L, 2.5 g / L, etc., and all ranges and sub-ranges between the above values; it should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.
[0039] In some embodiments of the present application, in step 2, the electrolyte includes sodium silicate, sodium hydroxide and sodium fluoride; wherein, in the electrolyte, the concentration of sodium silicate is 5-10 g / L, the concentration of sodium hydroxide is 1-4 g / L, and the concentration of sodium fluoride is 1-4 g / L. With this electrolyte, a sufficient amount of ZIF-7 can be grown on the surface of the micro-arc oxidation coating, while if an electrolyte with other components is used, it will cause difficulty in the growth of ZIF-7, and the amount grown is very small, which ultimately leads to insufficient uniformity and integrity of the grown ZIF-7. After research, the present application found that the above problems may be caused by the lack of sodium fluoride or the sodium fluoride is not controlled within the concentration range described in the present application. Therefore, in the electrolyte, the concentration of sodium silicate can be 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L, etc., and all ranges and sub-ranges between the above values; the concentration of sodium hydroxide can be 1 g / L, 2 g / L, 3 g / L, 4 g / L, etc., and all ranges and sub-ranges between the above values; the concentration of sodium fluoride can be 1 g / L, 2 g / L, 3 g / L, 4 g / L, etc., and all ranges and sub-ranges between the above values; it should be understood that, in an embodiment, any of the above ranges can be combined with any other ranges.
[0040] In some embodiments of the present application, the ZIF-7 seed solution is obtained by the following steps:
[0041] Dissolve zinc nitrate hexahydrate in N,N-dimethylformamide solution as solution A;
[0042] Subsequently, benzimidazole was dissolved in methanol of the same mass as that of solution A to form solution B;
[0043] Then, liquid A is slowly added to liquid B and stirred continuously to obtain the ZIF-7 seed solution. The room temperature can be maintained throughout the process, so that the pH value of the overall seed solution is less than or equal to 7, ensuring that the entire system is in a weakly acidic or neutral state. The pH value range is further preferably between 4 and 7. Too low a pH value will cause certain corrosion to the micro-arc oxidation layer.
[0044] In some embodiments of the present application, in step 2, the conditions of micro-arc oxidation treatment are as follows:
[0045] Current density is 6~10A / dm 2 , frequency is 500-800 Hz, duty cycle is 10%-50%, and micro-arc oxidation time is 5-15 min.
[0046] 2. Examples and Comparative Examples
[0047] The examples and comparative examples of the present application were all tested using AZ31B magnesium alloy.
[0048] Example 1
[0049] Step 1: Workpiece processing: AZ31B magnesium alloy is selected as the material of micro-arc oxidation anode, and it is processed into a rectangular specimen of 30mm×25mm×5mm. A hole with a diameter of 3mm is drilled just above the top of the specimen. The specimen is polished with 180#, 400#, 600#, 1200#, and 2000# water-abrasive sandpaper in turn until the surface of the material is smooth and there are no obvious scratches and pits; the polished AZ31B magnesium alloy workpiece is immersed in room temperature ethanol for ultrasonic cleaning for 20s, cleaned 2 to 3 times, and dried with cold air.
[0050] Step 2: Preparation of micro-arc oxidation film on magnesium alloy: add 8g / L sodium silicate, 2g / L sodium hydroxide, and 2g / L sodium fluoride to 1.5L deionized water, and add deionized water to 2L after fully dissolving, and stir for 8min to fully disperse it in the electrolyte. The total volume of the final prepared electrolyte is 2L. The pre-treated magnesium alloy workpiece is placed in the prepared electrolyte as the anode, and graphite is used as the cathode. The distance between the cathode and the anode is 12cm; a pulsed DC power supply is used to perform micro-arc oxidation on the magnesium alloy workpiece in constant current mode. The micro-arc oxidation parameters are: current density 6A / dm 2 , frequency 500Hz, duty cycle 30%, micro-arc oxidation time 10min. During the micro-arc oxidation process, the electrolyte was continuously stirred by a magnetic stirrer at a stirring speed of 800rpm. The test used a graphite double cathode, which was placed on both sides of the workpiece, with a distance of 12cm between the cathode and the anode. After the treatment, the prepared micro-arc oxidation composite film layer was cleaned with deionized water and blown dry.
[0051] Step 3: Preparation of in-situ grown ZIF-7 membrane layer: Place the sample obtained in step 2 in deionized water and ultrasonically clean it for 1 minute, and then dry it in a 60°C forced air drying furnace for 1 hour. After drying, take out the sample, rinse it with methanol and dry it naturally. Weigh 0.496g of zinc nitrate hexahydrate, place it in 70ml DMF, and then stir it until it dissolves. The solution is named liquid A. Add 0.551g of benzimidazole to 70ml methanol solution and stir it until it dissolves. The solution is named liquid B. Under constant stirring, liquid A is slowly added to liquid B through a disposable dropper, and it is stirred continuously. After stirring for a period of time, ZIF-7 seed solution is obtained. The sample is placed in the seed solution, and then placed in a reactor and kept warm for 4 hours at a temperature of 110°C. After insulation, the obtained sample is placed in deionized water and ultrasonically cleaned for 1 minute, and then dried in a 60°C forced air drying furnace for 1 hour. After drying, take out the sample.
[0052] Example 2
[0053] The method is adjusted based on Example 1, except that the heat preservation time is 3 hours. The other steps are exactly the same as those in Example 1.
[0054] Example 3
[0055] The method is adjusted based on Example 1, except that the heat preservation time is 5 hours. The other steps are exactly the same as those in Example 1.
[0056] Example 4
[0057] The adjustment was made on the basis of Example 1, except that the reaction temperature was 130° C. The other steps were exactly the same as those in Example 1.
[0058] Comparative Example 1
[0059] The method is adjusted based on Example 1, except that step 3 is not performed. The other steps are exactly the same as those in Example 1.
[0060] 3. Performance Analysis
[0061] 1. Microscopic morphology
[0062] Figure 1 The surface micromorphologies of the films prepared in Example 1 and Comparative Example 1 are shown respectively. It can be observed from the micromorphology of Comparative Example 1 that there are many micropores and cracks on the surface of the film prepared by the micro-arc oxidation (MAO) process. These defects may be caused by high-temperature local discharge during the MAO process, resulting in uneven internal structure of the film and poor density, thereby affecting the overall performance of the film. In comparison, the micro-arc oxidation composite film of Examples 1 to 4 shows significant improvements, and the flaky ZIF-7 film evenly distributed on the surface effectively fills the micropores and cracks. The formation of this flaky structure not only optimizes the density of the film surface, but also significantly improves its corrosion resistance, providing the possibility of further improving the function of the film.
[0063] The X-ray diffraction (XRD) pattern of Example 1 is as follows: Figure 2 As shown, by comparing it with the diffraction pattern of standard ZIF-7, it can be found that Example 1 has obvious diffraction peaks at positions such as 10 °, 15 ° and 20 °, which is basically consistent with the characteristic diffraction peak position of ZIF-7, but the intensity is different, which shows that the film layer of Example 1 successfully grows a ZIF-7 film layer with a clear crystal structure on the basis of micro-arc oxidation. At the same time, the appearance of these diffraction peaks not only confirms the existence of ZIF-7, but also shows that the ZIF-7 prepared by Example 1 has a higher degree of crystallinity, indicating that the crystal growth process is relatively complete and uniform, and has a good bonding effect with the basement film layer. The same result is obtained by analyzing the XRD patterns of other embodiments.
[0064] 2. Corrosion resistance
[0065] Figure 3 The electrochemical impedance test results of the film layers prepared in Examples 1 to 4 and Comparative Example 1 are shown. It can be clearly seen from the figure that compared with Comparative Example 1, the film layers of Examples 1 to 4 exhibit significantly higher impedance values. This shows that the electrochemical properties of the film layers have been significantly optimized through the preparation processes of Examples 1 to 4. Specifically, the impedance values of the film layers of Examples 1 to 4 in the electrolyte environment increase, indicating that they have better shielding effects on corrosive media, thereby effectively improving the corrosion resistance of the film layers. This increase in impedance may be closely related to the optimization of the microstructure of the film layer and the reduction of surface defects. In addition, the higher impedance value reflects the stronger stability of the film layer in the electrochemical system, providing reliable support for its corrosion resistance in practical applications.
[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the technical solution. Ordinary technicians in this field should understand that those modifications or equivalent substitutions of the technical solution of the present application that do not depart from the purpose and scope of the technical solution of the present application should be included in the scope of the claims of the present application.
Claims
1. A method for in-situ growth of a ZIF-7 film on the surface of a magnesium alloy micro-arc oxidation film, characterized in that: The specific steps include: Step 1: Process the surface of the magnesium alloy workpiece to be processed to make the surface smooth; Step 2: placing the workpiece treated in step 1 as an anode in an electrolyte, using graphite as a cathode, and performing micro-arc oxidation treatment on the workpiece using a DC power supply in a constant current mode to form a micro-arc oxidation film layer on the surface of the workpiece, followed by cleaning and drying; Step 3: Place the workpiece prepared in step 2 into a ZIF-7 growth solution, keep it at 110-130°C for 180-300 minutes for in-situ growth, take it out after the growth is completed, and wash and dry it; The ZIF-7 seed solution includes zinc nitrate hexahydrate and benzimidazole, and the solvent is N,N-dimethylformamide and methanol; in the ZIF-7 seed solution, the concentration of zinc nitrate hexahydrate is 0.5-2.5 g / L, and the concentration of benzimidazole is 0.5-2.5 g / L.
2. The method according to claim 1, characterized in that: In step 2, the electrolyte includes sodium silicate, sodium hydroxide and sodium fluoride; wherein, in the electrolyte, the concentration of sodium silicate is 5-10 g / L, the concentration of sodium hydroxide is 1-4 g / L, and the concentration of sodium fluoride is 1-4 g / L.
3. The method according to claim 1, characterized in that: The ZIF-7 seed solution is obtained by the following steps: Dissolve zinc nitrate hexahydrate in N,N-dimethylformamide solution as solution A; Subsequently, benzimidazole was dissolved in methanol of the same mass as that of solution A to form solution B; Then, liquid A is slowly added into liquid B while stirring continuously, and the ZIF-7 seed solution is obtained by mixing.
4. The method according to claim 1, characterized in that: In step 3, the temperature range is preferably 110°C to 130°C.
5. The method according to claim 1, characterized in that: In step 3, the holding time is preferably 180 to 300 minutes.
6. The method according to claim 1, characterized in that: In step 1, the surface of the magnesium alloy workpiece is polished to make the surface smooth using water-abrasive sandpaper with mesh sizes of 180#, 400#, 600#, 1200#, and 2000#, respectively.
7. The method according to claim 1, characterized in that: In step 2, the electrolyte was continuously stirred at a speed of 800 rpm.
8. The method according to claim 1, characterized in that: In step 3, the pH value of the seed solution is less than or equal to 7.
9. The method according to claim 1, characterized in that: In step 2, the conditions of the micro-arc oxidation treatment are as follows: Current density is 6~10A / dm 2 , frequency is 500-800 Hz, duty cycle is 10%-50%, and micro-arc oxidation time is 5-15 min.
Citation Information
Patent Citations
Micro-arc oxidation magnesium alloy surface one-step in-situ generated Zn-MOF coating and preparation method thereof
CN113668035A
Preparation method of self-repairing anti-corrosion coating based on ZIFs
CN116004086A
Method for secondary growth of ZIF-8 film layer on surface of aluminum alloy micro-arc oxidation film layer
CN117568799A
Cited By
Method for preparing super-hydrophobic coating on alloy surface
CN122854949A